Pemberdayaan Bibit Mangrove Sebagai Alternatif Edukasi Pengembangan Wisata Di Desa Muara Kecamatan Suranenggala Kabupaten Cirebon - Vany Dwi Putri; Tapsila Tapsila; Linda Septimia (Etos : Jurnal Pengabdian Masyarakat, 2021)
Coastal areas tend to experience soil erosion along the coast, as a result floods often occur due to this. As a result, land on the edge of a river near the sea experiences soil erosion, although the impact is not too big, if left unchecked, it will result in flooding in the future. Therefore, we are trying to plant mangroves with the aim of opening up insights on the importance of environmental conservation and how to maintain the balance of the ecosystem in it and to hone care for the river area in Muara Village. Apart from its usefulness as preventing soil abrasion or erosion, mangroves also have their own aesthetic beauty. . The method used in this activity was counseling on the use of mangrove trees and mangrove tree planting practices. The counseling stage in the form of material delivery and mangrove planting practices was carried out in the Bengawan Celancang river, Muara Village, Suranenggala District, Cirebon Regency. With the activities that we carry out, it is intended that every resident of Muara Village can pay more attention to the mangrove ecosystem. As well as being an inspiration for other villages that are located on the coast of Cirebon Regency. Abstrak Daerah pesisir cenderung mengalami pengikisan tanah di pinggir pantai, akibatnya tidak jarang terjadinya banjir karena hal tersebut. Tanah yang ada di pinggir sungai dekat laut akibatnya mengalami pengikisan tanah, meski dampaknya tidak terlalu besar, namun jika dibiarkan akan mengakibatkan kebanjiran di kemudian hari. Maka dari itu, kami mengupayakan penanaman mangrove bertujuan untuk membuka wawasan akan pentingnya kelestarian alam lingkungan dan bagaimana menjaga keseimbangan ekosistem di dalamnya serta mengasah kepedulian terhadap daerah sungai di Desa Muara.Selain karena kegunaannya sebagai mencegah abrasi atau pengikisan tanah, mangrove juga memiliki keindahan estetika tersendiri.Metode yang digunakan dalam kegiatan ini adalah penyuluhan mengenai pemanfaatan pohon mangrove dan praktik penanaman pohon mangrove. Tahap penyuluhan berupa penyampaian materi dan praktik penanaman mangrove dilaksanakan di sungai Bengawan Celancang Desa Muara Kecamatan Suranenggala Kabupaten Cirebon. Dengan adanya kegiatan yang kami lakukan ini bertujuan agar setiap warga Desa Muara dapat lebih memperhatikan ekosistem mangrove. Serta dapat menjadi inspirasi bagi Desa-desa lain yang letaknya berada di pinggir pantai